The Impact of Project Based Learning on Enhancing Students Critical Thinking and Self Efficacy in Classification of Living Things - Ismaini, Mauli; Rahmatan*, Hafnati; Djufri, Djufri; Samingan, Samingan; Safrida, Safrida; Zai, Sajid Ali Yousuf (Universitas Syiah Kuala, 2025)
The educational demands of the 21st century emphasize the importance of equipping learners with essential skills such as critical thinking and self-efficacy. Critical thinking skills (CTS) enable learners to analyze, evaluate and solve problems logically. Self-efficacy reflects learners' belief in their ability to face learning challenges. This study aims to analyze the impact of project-based learning (PjBL) model implementation towards learners' CTS and self-efficacy on the material of classification of living things, and explore the relationship between self-efficacy and CTS. The method used in this research is quasi-experiment with pretest-posttest non-equivalent control group design. Data collection was carried out using a CTS test instrument with indicators developed by Ennis, and a self-efficacy questionnaire developed by May. Data analysis used independent sample t-test and pearson product moment with a significant level of = 0.05. The results of the research on CTS parameters showed a sig value. 0.000 0.05. The results of research on self-efficacy parameters show in the moderate category. The results of research on the relationship between self-efficacy and CTS show a sig value. 0.021 0.05. The data analysis can be concluded that there is an effect of applying the PjBL model on improving students' CTS. Self-efficacy of students in the experimental class after the intervention was in the moderate category. A low and positive relationship exists between self-efficacy and CTS of students